Fundamentals of project management - Heagney, Joseph (American Management Association (AMACOM), 2016)
Project mishaps are all too common but often easy to avoid. Fundamentals of Project Management gets both new and current managers up to speed on the basics-the first crucial step for completing projects timely and on budget. Having already helped many generations of project managers navigate the ins and outs of every aspect of successful project management, this revised edition remains the perfect resource for succeeding in this complex discipline that has changed greatly in recent years.